(3CSGSjGJ GdHQeLI HGSJYeGd (BVisual Basic.nets - (3YRH eMeO(B, (3YRHs ((3GdbGgQI(B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B,s, 2004)
(3ebOeI Yf (Bvisual studio.net - (3eQHY GdGOhGJ (Btool box- (3bhGYO GddZI(B- (3NGUjI GdJhQjK (Binheritance- (3ebOeI Yf bhGYO GdHjGfGJ (Bintroduction to datadbase- (3eYGdLI GdGNWGA (Bdebugs
Keywords: Visual Basic.net; (3GdHQeLjGJs; (3Yde GdMGShHs